Transportation of perishable goods by air: handling problems at Russian airports - I. O. Poleshkina (Naučnyj Vestnik MGTU GA, 2020)
The article deals with the problems of perishable goods handling process at Russian airports on delivery in international supply chains (ISC). The investigation was carried out on the basis of operational analysis. The initial stage of the study, which was performed applying statistical analysis, revealed that the major category of perishable goods which establish air transportation demand into Russia is the fresh exotic fruits. The investigation was performed taking the mango supply chain as an example, due to its non-standard thermal and storage requirements. The second stage resulted in the perishable goods airport handling quality criteria set formation: the number of mandatory cargo while handling operations, the required time for these operations, the amount of paper work, the number of multi-temperature chambers at the airport and their area, ULD temperature storage system availability. The study revealed that about 90% of perishable goods, which are imported to Russia, are handled at the airports of Moscow aviation hub because other airports in Russia lack the temperature storage facilities infrastructure. This restriction raises the price of perishable goods logistics on the territory of the country considerably as well as reduces their quality. Four international airports of strategic importance outside the boarders of the central federal district which have the potential of forming central hubs for perishable goods handling as well as processing of transit and transfer flows were chosen in the context of this study. Among them are the airports of Novosibirsk, Vladivostok, Yekaterinburg and Krasnoyarsk. The airports of Moscow aviation hub were offered specialization on the subject of perishable goods export-import flow handling. The materials received from airlines, major cargo terminals at Russian airports, transport companies, specialized international air transport enterprises and logistics associations were exploited as the data for this study. The research registered that the deterrence to the speed of supply chain operation is the time of cargo ground service at Russian airports which considerably exceeds the cargo ground service time in the exporting country. The delays are connected with the poor development of perishable goods handling cargo terminals and also with loads of paper work because the system of electronic workflow and automated checking of markings doesn’t exist. The model of electronic workflow in the International Supply Chain which utilizes pre-flight and pre-loading preliminary information about the cargo was offered. Block Chain system for checking the correct presentation of documents at all stages of the supply chain was introduced which reduces the total time of cargo ground handling process.